2020
DOI: 10.1186/s12917-020-02500-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of piroplasm infection in companion animals in Hunan Province, China

Abstract: Background Feline and canine babesiosis is an important tick-borne disease caused by parasites of the genus Babesia. The disease has a worldwide distribution and causes serious health problems in domestic and wild canidae and felidae. Results Genomic DNA was isolated from blood samples, which were randomly collected from pet dogs ( n = 115) and cats ( n = 25) in Changsha city of Hunan Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
6
2
Order By: Relevance
“…For feline Babesia species, B. vogeli was found in three of 203 cats in China [ 20 ], and has been reported in Thailand, Portugal and Brazil [ 30 , 31 , 32 ]. In other studies, one cat was diagnosed with B. hongkongensis in Hong Kong and two cats were positive for B. hongkongensis in Hunan [ 23 , 24 ]. For the presence of B. gibsoni in cat, there was just one reported in St Kitts [ 21 ], and B. gibsoni was considered to be a species responsible for canine babesiosis in China, including Shanghai, Jiangsu, Shandong, Anhui, Zhejiang, Jiangxi, Fujian, Hubei and Shaanxi with positivity 0.72% to 64.2% [ 15 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For feline Babesia species, B. vogeli was found in three of 203 cats in China [ 20 ], and has been reported in Thailand, Portugal and Brazil [ 30 , 31 , 32 ]. In other studies, one cat was diagnosed with B. hongkongensis in Hong Kong and two cats were positive for B. hongkongensis in Hunan [ 23 , 24 ]. For the presence of B. gibsoni in cat, there was just one reported in St Kitts [ 21 ], and B. gibsoni was considered to be a species responsible for canine babesiosis in China, including Shanghai, Jiangsu, Shandong, Anhui, Zhejiang, Jiangxi, Fujian, Hubei and Shaanxi with positivity 0.72% to 64.2% [ 15 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 21 , 22 ]. In China, B. vogeli has been reported in cats in Shenzhen and B. hongkongensis was found in cats in Hong Kong and Hunan [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…infecting dogs has been found in 11 provinces and one municipality of China, with a highest frequency of B. gibsoni, followed by B. vogeli (Jin et al, 2005;Xu et al, 2015;He et al, 2017;Niu et al, 2017;Zhang et al, 2017;Zheng et al, 2017;Li et al, 2020;Wang et al, 2020). A recent study showed that four dogs (3.5%) were positive for B. canis, and one for B. vogeli (0.87%) in Hunan province of China (Wang et al, 2020). However, in the present study, B. gibsoni and B. vogeli have been detected, but no B. canis.…”
Section: Discussionmentioning
confidence: 99%
“…infection in Hunan province, subtropical China. Importantly, a recent study has indicated that B. canis is the most widespread species in Hunan province (Wang et al, 2020). Therefore, the objective of the present study was to investigate the prevalence of Babesia spp.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation